P01 Bacterial meningitis in infants <90 days of age: Assessment of healthcare delivery. (7th April 2014) - Okike, IO; Ninis, N; Henderson, KL; Blackburn, RM; Muller-Pebody, B; Johnson, AJ; Anthony, M; Heath, PT
Abstract : Background: Bacterial meningitis in infants <90 days of age remains a significant cause of mortality and morbidity. Despite all the existing prevention and management strategies, recent UK study (2010–2011) showed that the incidence and case fatality rate has not changed over the last two decades. Data on the detailed early case management of bacterial meningitis in this age group is lacking. We therefore set out to assess in detail the healthcare delivery of the management of bacterial meningitis among this age group in order to formulate better management strategies to improve outcome. Methods: We conducted a detailed review of the medical records of infants with bacterial meningitis whose parents consented to take part in England and Wales between September 2010 and June 2013. Parents completed a questionnaire with details of the timing of onset and progression of features. All stages of care, including pre-hospital management, initial hospital assessment and ongoing care, post admission follow up were assessed. Ethics approval was by Cambridgeshire 2 REC (Ref: 10/H0308/64). Results: During the study period 103 parents consented and 97 were confirmed cases. 66 (68%) were admitted from home and 31 (32%) were already in hospital prior to the onset of the meningitis. The median age was14 days (IQR 3–25) and was higher in home admissions 17 days (11–34) compared to cases already in hospital 1 day (0–7), p = 0.0001. Most 52 (54%) were males and 73 (76%) were born at term. Amongst cases admitted from home, 38% encountered inappropriate pre-hospital management. The median time (IQR) from onset of symptoms to first help was 4.8 h (2–10), triage to first dose of antibiotics was 1.7 h (1.0–3.3) and 54% received empiric antibiotics that were not as per NICE bacterial meningitis guideline. For cases in hospital already, the median time from onset to first dose of antibiotics was 2.6 h (1.3–k8.5) whilst 54% received empiric antibiotics that were not as per NICE bacterial meningitis guideline. Discussion: The quality of clinical care for bacterial meningitis in infants <90 days needs improvement. This study provides the first national data on the quality of care and provides rationale for developing targeted interventions to improve outcome.